Rare and Fatal Complication: A Case of Ketorolac-Induced Anaphylaxis Leading to Cardiac Arrest and Hypoxic-Ischemic Brain Injury in a Young Adult - Yogi Ramadhan; Pratama Ananda; Novita Anggraeni (HM Publisher, 2025)
Background: Anaphylaxis is a severe, life-threatening allergic reaction that can lead to cardiac arrest and hypoxic-ischemic brain injury (HIBI). Ketorolac, a nonsteroidal anti-inflammatory drug (NSAID) commonly used for postoperative pain management, has been rarely associated with anaphylaxis. Case presentation: We present the case of a 32-year-old woman who developed anaphylaxis and subsequent cardiac arrest following intravenous administration of ketorolac after an appendectomy. Despite successful resuscitation, the patient suffered from HIBI and remained in a persistent vegetative state. Conclusion: This report highlights the potential for fatal complications associated with ketorolac administration and emphasizes the importance of prompt recognition and management of anaphylaxis in the perioperative setting. This case underscores the need for heightened vigilance regarding potential anaphylactic reactions to ketorolac, even in patients with no prior history of drug allergies. Early recognition and aggressive management of anaphylaxis are crucial to minimize the risk of severe complications like cardiac arrest and HIBI.